2022
DOI: 10.3390/ijms23169430
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of Toll-like Receptor 4 in Hepatocellular Carcinoma—A Single-Center Study

Abstract: Hepatocellular carcinoma (HCC) is the most common primary liver tumor leading to significant morbidity and mortality; its exact genetic background is largely unrecognized. Toll-like receptor-4 (TLR4) reacts with lipopolysaccharides, molecules found in the outer membrane of Gram-negative bacteria. In damaged liver, TLR4 expression is upregulated, leading to hepatic inflammation and injury. We tried to investigate the role of the two most common single-nucleotide polymorphisms (SNPs) of TLR4 in HCC-genesis. Aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…HCC is one of the most common malignant tumours, with a low survival rate globally. The specific mechanism of HCC occurrence has not been fully elucidated, due to its complexity and diversity of the pathogenesis, 23 – 26 and clinical treatments still lack effective therapeutic strategies. Metformin is currently used as a first-line drug treatment for T2D.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is one of the most common malignant tumours, with a low survival rate globally. The specific mechanism of HCC occurrence has not been fully elucidated, due to its complexity and diversity of the pathogenesis, 23 – 26 and clinical treatments still lack effective therapeutic strategies. Metformin is currently used as a first-line drug treatment for T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed disparities in HCC among females compared to males in terms of undergoing HCC surveillance, tumor size at diagnosis, and vascular involvement [ 13 , 14 ]. Previous studies showed that older age, male sex, the severity of compensated cirrhosis at presentation, and sustained activity of liver disease are important predictors of HCC [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Mousa et al [ 280 ] did not find any link between rs4986791 C/T and POAG in a study on the Saudi population with a much smaller sample size. Evidence suggests that these functional polymorphisms promote apoptosis in hepatic stellate cells by decreasing Bcl-2 [ 284 , 285 ], although the roles of these mutations are controversially discussed for various diseases. The polymorphisms rs4986790 A/G and rs4986791 C/T were therefore proposed to promote RGC apoptosis [ 277 ].…”
Section: Microbiome Dysbiosis At the Intersection Of Obesity And Glau...mentioning
confidence: 99%